Pre-service biology teacher’s perception on local environment problems as contextual learning resources - Ahmad Yani; Mohamad Amin; Fatchur Rohman; Endang Suarsini; Muhammad Rijal (Institute of Advanced Engineering and Science, 2021)
A survey and exploratory study were conducted to analyze Lake Tempe as a resource for contextual learning (CTL). The first phase of the study included exploring the lake’s potential through interviews with the people who live in the lake’s coastal region. Quadrat transects were done to identify aquatic plants around the lake. A feasibility analysis was conducted to see the lake’s potential as a learning resource. Field data were collected and compared to the environmental biology (EB) curriculum, responses, and learning outcome. The data were analyzed descriptively and tested using a paired-sample t-test. The results showed differences in the three stations’ physicochemical parameters and decreased quality of the water. It was found that anthropogenic activity had a significant contribution to the lake’s pollution. Nine species of six aquatic plant families were found in the lake. The survey revealed that the lake was feasible as a learning resource with criteria easy to access, safety, time efficiency, costs, and the material's suitability for EB courses. The t-test showed a difference in the students’ scores between before and after exploration practices. These findings suggest that Lake Tempe can serve as a resource for CTL in EB courses.